Japanese Vocabulary Acquisition Through Anime: A Case Study On Dwimeilinda - Virgi Marlany Ibnatul Karimah; Fahriany Fahriany; Firdaus Habibi (IZUMI, 2019)
(Japanese Vocabulary Acquisition through Anime: A Case Study on Dwimeilinda) This study attempted to investigate the influence of watching anime on Japanese vocabulary acquisition from Dwimeilinda. The study used a mixed-method. There are three collection data in this study; the first data is the interview; the second is observation; the last is the aural test. There are two questions from this study: first, how did she acquire the vocabulary through anime? Second. How is the influence of watching anime on her Japanese vocabulary acquisition? The results showing there are some strategies that she uses in acquiring Japanese vocabulary. First repetition, second cognate and third is mind mapping. The study also found that watching anime can influence her phonological vocabulary knowledge and daily expression.    gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor